Sedimentology of Passive Margin Sequences in the Northern Carnarvon Basin and Implications for Variations in Seismic Velocity - Winata, Mulky (Curtin University, 2024)
The passive margin sequence of the Northern Carnarvon Basin comprises distinct sequences that correspond to periods of post -rift subsidence, bottom current activity and mass transport complex deposition. These different phases of evolution can be related to the progressive separation of Australia from Gondwana.